ACKNOWLEDGMENTS. (Language Without Soil: Adorno & Late Philosophical Modernity, 2010)
People that the author would like to thank for their assistance in the creation of the book "Language Without Soil: Adorno and Late Philosophical Modernity," are mentioned.